2015
DOI: 10.1111/echo.13007
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Ultrasound Maximum Plaque Height–A Sensitive Imaging Biomarker for the Assessment of Significant Coronary Artery Disease

Abstract: Increased carotid intima-media thickness and plaque measurements are indicative of the presence of epicardial coronary stenosis. Plaque burden is a more sensitive imaging biomarker for ruling out significant coronary artery disease, including in younger individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 29 publications
1
36
0
1
Order By: Relevance
“…9,11,12,22 A meta-analysis of 11 studies also supported this finding. 9,11,12,22 A meta-analysis of 11 studies also supported this finding.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…9,11,12,22 A meta-analysis of 11 studies also supported this finding. 9,11,12,22 A meta-analysis of 11 studies also supported this finding.…”
Section: Discussionmentioning
confidence: 73%
“…with low frequency but severe risks. 12 However, few studies have focused on the total number of plaques. Atherosclerosis plays a key role in the pathogenesis of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of 500 ultrasound examinations carried out on patients 1 day prior to their undergoing a coronary angiogram revealed an 87% level of sensitivity in predicting a coronary stenosis of at least 50% following a type III or IV b ultrasound finding [1]. A further study which was conducted revealed similar results [7]. The follow-up study to date has demonstrated that subjects with advanced atherosclerosis (type III or type IV b findings) are at significantly increased risk of having cardiovascular disease.…”
Section: Discussionmentioning
confidence: 98%
“…The CIMT was measured in the far wall distal CCA and the mean of both sides was used for analysis. Carotid plaque height was measured in the bulb and ICA as previously described, and the maximum of either side was used for analysis …”
Section: Methodsmentioning
confidence: 99%
“…The extent of CAD from angiography was quantified using a previously established angiographic score. 14,15 Briefly, a score of zero represented no coronary lesions, one represented mild disease (0-25% stenosis of at least one artery), two represented moderately significant disease (25-50% stenosis of at least one artery), and three represented severe disease (>50% stenosis of at least one artery). The high inter-rater reliability for this method was previously established by Johri and colleagues.…”
Section: Carotid Ultrasound and Speckle Tracking Strain Analysismentioning
confidence: 99%